Information society : evolving landscapes - Berleur, Jacques ed. [et al]... (Springer-Verlag New York Inc. New YorkUS, 1990)
Provides a variety of perspectives on the many complex issues raised by the growing reliance on information technologies. Examines aspects such as ethics; roots, legitimacy and ideology; culture; politics; economics; and artificial intelligence, human mind and image of reality.